Efektivitas Penanganan Dugaan Pelanggaran Hak Asasi Manusia di Kantor Wilayah Kementerian Hukum dan HAM Sumatera Utara - Simatupang, Riris; Simamora, Janpatar (Lembaga Dongan Dosen, 2025)
The Republic of Indonesia recognizes and upholds human rights and basic human obligations. Rights that are inherent and cannot be separated from humans. It must be protected, respected and upheld for the sake of increasing human dignity, welfare, happiness, intelligence and justice. For this reason, the researcher raised the title Effectiveness of Handling Alleged Human Rights Violations at the Office of the Ministry of Law and Human Rights in North Sumatra. Handling of alleged human rights violations is carried out for every act carried out by a person or group, whether intentionally or unintentionally or by negligence which is unlawful. With the increasing number of alleged human rights violations, the North Sumatra Regional Office of the Ministry of Law and Human Rights provides policies related to public services in order to provide needs in accordance with statutory regulations for every citizen. The Sumatra Utara Regional Ministry of Law and Human Rights Office provides quality operational and handling services.